Evaluation of array antenna systems for global navigation satellite system applications using wave‐field synthesis in an over‐the‐air laboratory. Issue 4 (22nd January 2018) - Schirmer, Christopher; Rügamer, Alexander; Kotterman, Wim A.T.; Landmann, Markus; Del Galdo, Giovanni
Abstract : Antenna characterisation is usually performed by antenna pattern measurements in an anechoic chamber. Subsequently, a conducted test, the radiated two‐stage or the wireless‐cable method can be used for an overall system evaluation considering the measured patterns. In this study, the authors present a method to perform device tests for antenna arrays/smart antennas with and without the need of radiation pattern measurements, and they validate it experimentally. By using over‐the‐air tests in a virtual electromagnetic environment and wave‐field synthesis, the propagation environment can be realistically recreated in the region around a device‐under‐test. This allows for reproducible performance comparisons of different antennas or systems under identical propagation environment conditions. As a special application, they consider the controlled reception pattern antenna in a global navigation satellite systems environment in the presence of interferer signals.